2012
DOI: 10.1002/app.36607
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long chain branching on melt fractures in capillary extrusion of metallocene‐catalyzed linear low‐density polyethylene melts

Abstract: To investigate the effect of long chain branching (LCB) on melt fractures of metallocene-catalyzed linear low-density polyethylene (mLLDPE), we prepared a series of sparsely long-chain-branched mLLDPEs with well-defined degrees of LCB. Gross melt fractures were observed to decrease as the degree of LCB increases. This is in accordance with a prediction based on the observation that LCB enhances chain entanglement and consequently increases the melt strength of a polymer. However, sharkskin melt fracture (SMF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…The slope is also independent of MW, MWD, and the measurement conditions . The rheological properties discussed above are conventionally used for LCB characterization, but many other rheological parameters such as the first normal stress coefficient (ψ1) enhancement, the critical tensile stress ( σ c ) for the onset of gross melt fracture, the sharkskin periodicity and the stick‐slip flow in capillary extrusion experiments and so on can be also used.…”
Section: Rheological Characterizationmentioning
confidence: 99%
“…The slope is also independent of MW, MWD, and the measurement conditions . The rheological properties discussed above are conventionally used for LCB characterization, but many other rheological parameters such as the first normal stress coefficient (ψ1) enhancement, the critical tensile stress ( σ c ) for the onset of gross melt fracture, the sharkskin periodicity and the stick‐slip flow in capillary extrusion experiments and so on can be also used.…”
Section: Rheological Characterizationmentioning
confidence: 99%
“…[ 20 ] reported the opposite effect on a series of sparsely (less than two LCBs per 10 4 main chain carbons) long‐chain branched metallocene linear low‐density polyethylene (mLLDPE). [ 20 ] The surface patterns (cylindrical extrudates) identified included sharkskin and at higher shear rates gross melt fracture. [ 20 ] Filipe et al., [ 21 ] using an emerging state‐of‐the‐art high‐sensitivity piezoelectric pressure measurement system, included several LCB polymers in their study and reported surface and volume MFEI in some that they identified as sharkskin and stick‐slip.…”
Section: Introductionmentioning
confidence: 99%
“…However, Yoo et al [20] reported the opposite effect on a series of sparsely (less than two LCBs per 10 4 main chain carbons) long-chain branched metallocene linear low-density polyethylene (mLLDPE). [20] The surface patterns (cylindrical extrudates) identified included sharkskin and at b) typical extrudate patterns in a low-density polyethylene (LDPE). Both visualizations were performed on extrudates from Georgantopoulos et al [24] ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, metallocene‐catalyzed polyethylenes (mPEs) exhibit superior physical and mechanical properties because the metallocene catalyst yields polyolefins with a narrow molecular‐weight distribution and sparse long‐chain branches . Metallocene catalysis produces PE with an excellent degree of control over the molecular structure and stereospecificity at the commercial scale . In manufacturing, mPE is considered to be a good option among the available plastics because it has good mechanical properties.…”
Section: Introductionmentioning
confidence: 99%